Patterns of Cancer in Males and Females in Jammu Region - Ashutosh Gupta; Isha Puri; Meenu Gupta (Dr. Annil Mahajan, 2021)
Background: Cancer is a leading cause of mortality and morbidity in the world. There are marked differences in distribution of cancers in different regions of the world. Aim: The aim of the present study is to see the pattern of different cancers in Jammu region. Material and Methods: This is a retrospective study of histologically confirmed cases of all cancers registered at Regional Cancer Centre (RCC) Jammu from Jan.2017 to Dec.2018. Medical Record of cancer patients was used for collecting data. Results: A total of 4409 cancer cases were registered during this period, out of which males accounted for 2504 (56.79%) and females for 1905 (43.2%) cases with male to female ratio of 1.31:1. Most common age group in males (43.17%) was 60-80 yrs. and in females (48.81%) was 40-60yrs. Lung cancer was the most common cancer in males followed by cancers of Oral Cavity, Larynx, Oesophagus and Leukaemia. Breast cancer was the most common cancer in females followed by ca cervix, ca ovary, ca lung and ca oesophagus. Majority of males (37.8%) and females (42.3%) were from Jammu district and presented with Stage 4 - males (53.31%), females (36.58%). Chemotherapy alone was the most common treatment modality used in both males (48.4%) and females (26.50%). Conclusion: Lung Cancer was the most common cancer in males followed by Head and Neck cancers. Breast cancer was the most common cancer in females followed by cervical cancer. These patterns provide comprehensive information on cancer occurrence and valuable leads to cancer control in this region.